Surface Phenotype Changes and Increased Response to Oxidative Stress in CD4+CD25high T Cells - Yoshiki Yamamoto; Takaharu Negoro; Rui Tada; Michiaki Narushima; Akane Hoshi; Yoichi Negishi; Yasuko Nakano (Biomedicines, 2021)
Conversion of CD4+CD25+FOXP3+ T regulatory cells (Tregs) from the immature (CD45RA+) to mature (CD45RO+) phenotype has been shown during development and allergic reactions. The relative frequencies of these Treg phenotypes and their responses to oxidative stress during development and allergic inflammation were analysed in samples from paediatric and adult subjects. The FOXP3lowCD45RA+ population was dominant in early childhood, while the percentage of FOXP3highCD45RO+ cells began increasing in the first year of life. These phenotypic changes were observed in subjects with and without asthma. Further, there was a significant increase in phosphorylated ERK1/2 (pERK1/2) protein in hydrogen peroxide (H2O2)-treated CD4+CD25high cells in adults with asthma compared with those without asthma. Increased pERK1/2 levels corresponded with increased Ca2+ response to T cell receptor stimulation. mRNA expression of peroxiredoxins declined in Tregs from adults with asthma. Finally, CD4+CD25high cells from paediatric subjects were more sensitive to oxidative stress than those from adults in vitro. The differential Treg sensitivity to oxidative stress observed in children and adults was likely dependent on phenotypic CD45 isoform switching. Increased sensitivity of Treg cells from adults with asthma to H2O2 resulted from a reduction of peroxiredoxin-2, -3, -4 and increased pERK1/2 via impaired Ca2+ response in these cells.